Carbon Isotopic Fractionation via Diffusion in a Coarse Material. (15th September 2018) - Schulte, M.; Jochmann, M. A.; Gehrke, T.; Denecke, M.; Schmidt, T. C.
Abstract: Methane oxidation is a major environmental process in different types of soil. Due to its global warming potential, exact fluxes of methane from soil to the atmosphere are relevant for atmospheric and carbon flux modeling. In this context the investigation of the methane oxidation turnover rates is often carried out by measuring the isotopic fractionation during the involved biodegradation processes. Unfortunately, isotopic fractionation can be a result of both biodegradation and diffusion. Therefore, a thorough estimation of the diffusion‐related isotopic fractionation is mandatory for a correction of biotransformation relevant kinetic isotope effects. Here for the first time, we investigated the isotopic fractionation of methane by diffusion in a coarsely mixed crushed stone and soil material. Determined isotopic fractionations by diffusion in terms of enrichment factors were −0.0212 ± 0.005 at 22.5 °C and −0.0218 ± 0.003 at 30 °C. When estimating biotransformation of methane from stable isotope measurements, the fractionation by diffusion has to be subtracted for estimating correct biotransformation rates. The obtained data are relevant not only for the investigation of oxidation processes in landfills but can also be adapted to other coarse materials such as arctic and tundra as well as wetland and volcanic soils. As a consequence, including the isotopic fractionation by diffusion within calculations of biotransformation will allow determining more exact values under well‐known conditions for methane flux calculations. Key Points: Methane isotopic fractionation by diffusion was analyzed for a mixed‐crushed stone and soil material This study proves the applicability of an existing diffusion‐fractionation model on a coarse size material